International Legal Regulation in the Sphere of Pension Provision for Cis Citizens - Yu. V. Mishalchenko; L. A. Platonova; A. V. Toropygin (Евразийская интеграция: экономика, право, политика)
The present article analyzes the pension provision for citizens of the CIS integration associations and legal regulation prospects.In the article the fundamental documents on the pension provision regulation for CIS citizens are discussed, including international bilateral treaties of theRussian Federation.